From agents of the people to agents of authority? How illiberal populism impacts interactions between regulatory agencies and external stakeholders - Michael Dobbins; Rafael Labanino (Regulation & Governance, 2024)
The decline in democratic quality and the increasing electoral popularity of illiberal populist parties are among the most notable global phenomena in the past 200.167emyears. This article builds a bridge between the growing body of political science literature addressing how democratic backsliding impacts linkages between governments and organized interests and the public administration literature exploring how illiberal populists reshape the bureaucracy. Focusing on regulatory agencies in four post-communist countries that have recently experienced varying degrees of democrating backsliding, we explore whether and how interactions between bureaucrats and interest groups have changed amid democratic decline. We find that even in the context of backsliding, professionalization (i.e. internal organizational development) and expertise provision are strong positive predictors of interest groups' access to regulators. However, our analysis unequivocally shows that exclusion by illiberal populist incumbent parties has a profound and negative effect on organizations' ability to reach bureaucracies. ~We draw on a new survey dataset, which grasps relationships between organized interests and political institutions (i.e. governments, parties, regulatory agencies, parliaments) in the region.
Keywords: 330; Central and Eastern Europe; democratic backsliding; organized interests; politicization; populism; regulatory agencies